Evolutionary economics - Ulrich Witt (Max Planck Institute of Economics, 2006)
This article reviews the way of thinking about economic problems and the research agenda associated with the evolutionary approach to economics. This approach generally focuses on the processes that transform the economy from within and on their consequences for firms and industries, production, trade, employment and growth. The article highlights the major contributions to evolutionary economics and explains its key concepts together with some of their implications.
Keywords: 330